Innovations and adaptations in neonatal and pediatric respiratory care for resource constrained settings - Wu, Andrew; Mukhtar-Yola, Mariya; Luch, Sreyleak; John, Stephen; Adhikari, Bikash Raj; Bakker, Caitlin; Slusher, Tina; Bjorklund, Ashley; Winter, Jameel; Ezeaka, Chinyere (Frontiers in Pediatrics, 2022)
Respiratory disease is a leading cause of death in children under 5 years of age worldwide, and most of these deaths occur in low- to middle-income countries (LMICs) where advanced respiratory care technology is often limited. Much of the equipment required to provide advanced respiratory care is unavailable in these areas due to high costs, the need for specialty trained personnel, and myriad other resource constraints that limit uptake and sustainable use of these devices, including reliable access to electricity, sensitive equipment needing frequent maintenance, single-patient-use supplies, and lack of access to sterilization equipment. Compounding the problem, pediatrics is uniquely challenging in that one size does not fit all, or even most patients. Despite these substantial barriers, numerous innovations in respiratory care technology have been made in recent years that have brought increasing access to high quality respiratory care in some of the most remote areas of the world. In this article, we intend to review the global burden of respiratory diseases for children, highlight the prototypical innovations that have been made in bringing respiratory care to LMICs, spotlight some of the technologies being actively developed to improve respiratory care in resourceconstrained settings, and conclude with a discussion highlighting areas where further innovation is still needed.